2021
DOI: 10.1039/d0ra08009h
|View full text |Cite
|
Sign up to set email alerts
|

Laser activatable perfluorocarbon bubbles for imaging and therapy through enhanced absorption from coupled silica coated gold nanoparticles

Abstract: PFH-NEs from PFH-NEs-scAuNPs can vaporize upon laser excitation leading to formation of PFH bubbles that can be used for contrast enhanced US imaging and therapy.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…To achieve personalized treatment, CAP is emerging as a promising approach, as the parameters of the plasma device can be fine-tuned during the treatment to suit the patient's specific dosage. CAP has been shown to reprogram the tumor microenvironment [143][144][145], inhibit tumor growth with high selectivity, and even enhance the effectiveness of other treatment modalities like chemotherapy [146][147][148][149], immunotherapy [150,151], radiotherapy [152][153][154][155], and nanomedicine [156][157][158][159][160] with improved treatment outcomes and minimized sideeffects [161]. The self-adaptive nature of the adaptive plasma system complements the power of ML.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve personalized treatment, CAP is emerging as a promising approach, as the parameters of the plasma device can be fine-tuned during the treatment to suit the patient's specific dosage. CAP has been shown to reprogram the tumor microenvironment [143][144][145], inhibit tumor growth with high selectivity, and even enhance the effectiveness of other treatment modalities like chemotherapy [146][147][148][149], immunotherapy [150,151], radiotherapy [152][153][154][155], and nanomedicine [156][157][158][159][160] with improved treatment outcomes and minimized sideeffects [161]. The self-adaptive nature of the adaptive plasma system complements the power of ML.…”
Section: Discussionmentioning
confidence: 99%
“…ADV has a higher penetration depth, and it is consequently more efficient in phase transformation. [41][42][43] Some of the USCAs containing solid cores are summarized in Table 2.…”
Section: Uscas With a Liquid Corementioning
confidence: 99%
“…Secondly, researchers have demonstrated that therapeutic immune responses against cancer antigens by membrane disruption were stronger than those with tumor thermal ablation [42] and could enhance cancer cytotoxicity. Lastly, the formed bubbles can generate an additional signal for US contrast-enhanced ultrasound imaging [43,44]. We plan to further test dual-modal PA/US imaging efficacy upon particle vaporization and the bio-safety effect of ODV using our developed nanoparticles.…”
Section: Tissue Damage Evaluation Using Tunel and Hande Histology Analysismentioning
confidence: 99%